Impact of hyperthyroidism and its treatment on the outcome of mental health, occupational functioning, and quality of life: A naturalistic, prospective study - Roopa Chopra; Tejas Kalaria; Carolina Gherman-Ciolac; Rajeev Raghavan; Harit Narendra Buch; Nilamadhab Kar (Indian Journal of Psychiatry)
Context (Background): Hyperthyroidism has a major impact on mental health. Aims: We intended to determine the magnitude of the unmet need for mental health support in patients with hyperthyroidism attending an endocrinology clinic. Settings and Design: General Hospital Endocrine Department, Prospective Study. Methods and Material: In a naturalistic, prospective study, consecutive (n = 176) hyperthyroid patients were assessed for anxiety (generalized anxiety disorder, GAD-7), depression (Patient Health Questionnaire PHQ-9), functional impairment (work and social adjustment scale, WSAS), and quality of life (EuroQol ED5D) using standardized instruments. Statistical Analysis Used: Percentages, mean and standard deviation (SD), Chi-square, Student’s t-test, ANOVA, Spearman’s correlation Results: A considerable proportion (40.5%) of patients had moderate and severe anxiety, around half (50.6%) had moderate or severe depression, and 20.8% had severe functional impairment at presentation. Mean EQ5D score was 59.6 ± 23.5. The scores of anxiety, depression, and functional impairment were significantly correlated with each other and negatively correlated with QOL. Following treatment of hyperthyroidism, improvement in psychiatric symptoms was noted which could be correlated with the lowering of T4. However, a significant proportion of patients continued to have psychiatric symptoms and functional impairment despite achieving euthyroidism. There was no correlation between the severity of hyperthyroidism to persistence of mental health parameters. Conclusions: Our findings of high prevalence and persistence of impairment of mental health and functional status of patients with hyperthyroidism have highlighted the unmet needs for these patients.